THE EFFECTIVENESS OF hCG IN THE DYNAMICS OF FUNCTIONAL STRUCTURE OF SUPEROVULATED ACEH CATTLE OVARIES USING PREGNANT MARE SERUM GONADOTROPINS - Mitha Kurnia Sari; Iman Supriatna; Mohamad Agus Setiadi (Universitas Syiah Kuala, 2022)
This study aimed to determine the biopotency of pregnant mare serum gonadotropin (PMSG) in stimulating the formation of dominant follicles and the biopotency of human chorionic gonadotropin (hCG) in triggering an increase in the ovulation rate of the natural-estrus donor group and the prostaglandin F2α (PGF2α) induced group using female Aceh cattle (n= 20) which were divided into two treatment groups: the group with natural estrus (A) and the group with PGF2α -induced estrus (B). Each donor group was superovulated using the injection of PMSGhCG (A1, B1) and only PMSG (A2, B2). The observations on total follicles and CL were carried out at D10, D14/D+0 and D21/D+7 using ultrasonography (USG). The results showed that PMSG gave a better superovulatory response to the development of dominant follicles (P0.01) at A1, A2, B1, and B2. The administration of hCG hormone 2000 IU i.m. was not able to increase the rate of ovulation. Total follicles after the addition of hCG were also not significantly different between A1:A2 and B1:B2. Statistically, the number of CL in all donor groups in D21 was not significantly different (P0.05). It concluded, superovulation using PMSG gave the same results to the donor cows with natural estrus and the donor cows with PGF2α-induced estrus. The hCG hormone with a dose of 2000 IU injected i.m. was also not able to increase the ovulation rate of Aceh cattle superovulated with PMSG 2500 IU i.m. ____________________________________________________